MENGEMBANGKAN IKLIM ORGANISASI DI SEKOLAH DENGAN MENGGUNAKAN MODEL TAGIURI - Wahyono, Imam (JURNAL AL-TANZIM, 2019)
Organizational Climate is a subjective perception about the condition of a person in an organization that is sustainably maintained by involving all stakeholders, so that organizational goals can be achieved effectively and efficiently. If the organizational climate setting in an institution is positive, then the vision, mission and goals which are the ideals of the school will be effectively achieved. This research uses research library type research. The data analysis technique uses content analysis. Based on the results of research conducted by experts, including Tagiuri, argues that in developing the organizational climate in schools, there are four dimensions namely the ecological or environmental dimension, the social dimension, the social system and the culture that surrounds it. These four dimensions according to Taguiri include all dimensions in educational institutions to achieve the goals of the organization of educational institutions. Among the strategies that can be used to develop a positive organizational climate through these four dimensions, namely by making a policy or regulation by the Principal, where the policy leads to the improvement of organizations that are oriented to quality.